Urban Form and Productivity What Is the Shape of Latin American Cities? - Duque, Juan C. (The World Bank, 2019)
This paper examines the linkages between urban form and city productivity, using alternative metrics for urban form and applying them to a comprehensive sample of Latin American cities. Although most of the literature has concentrated on the effects of population density (compact versus sprawling urban development), this paper seeks to assess whether different dimensions of a city's urban form, such as shape, structure, and land-use, affect its economic performance. The paper finds that the shape of the urban extent, the inner-city connectedness, and fullness have a statistically significant influence on the productivity level of the city